Deduction and study of the general equation that determines the quantity of non-eluted materials by gas chromatography. Analysis of abused oils - A. Castellón Arnau (Grasas y Aceites, 1991)
The general equation that determines the quantity of noneluted materials in a chromatographic separation is deduced. This equation permits the calculation of these materials when the internal standard is not pure and when interfering substances of the oil are chromatographied with it. The obtained equation is applied in the quantification of the thermal-oxidative degradation products present in heated oils. The theoretical standard deviation of the values of the non-eluted materials is also calculated. The experimental study shows that there is a positive bias of the non-eluted materials if one does not consider the presence of interfering materials.